The Role of Midwives in Improving Compliance with Family Planning Programs in Underdeveloped Villages - Maisarah Alzena (Institute of Accounting Research and Novation (IARN), 2025)
Family planning (FP) programs are essential for improving maternal and child health, particularly in underdeveloped villages where access to health services is limited. Midwives play a crucial role as frontline health workers responsible for implementing and sustaining family planning programs in these settings. This study aims to explore and describe the role of midwives in improving compliance with family planning programs in underdeveloped villages, with a focus on the types of roles performed, the level of compliance among couples of reproductive age, and the impact of midwives’ interventions on community knowledge, attitudes, and behaviors related to family planning.A descriptive research design was employed involving midwives, couples of reproductive age, and community stakeholders in selected underdeveloped villages. Data were collected through questionnaires, in-depth interviews, observations, and document reviews. Family planning compliance was measured using indicators such as consistent contraceptive use, continuation of selected methods, and regular attendance at follow-up visits. Data were analyzed using both statistical and thematic approaches. The findings reveal that midwives carry out multiple roles, including health education, individualized counseling, contraceptive service provision, follow-up care, and community outreach. These roles contribute significantly to increased knowledge, more positive attitudes toward contraception, and improved compliance with family planning programs. Higher compliance levels were observed in communities where midwives actively engaged in culturally sensitive education and continuous follow-up. Overall, the study underscores the vital role of midwives in enhancing family planning compliance and highlights the importance of strengthening midwife capacity and community-based strategies to improve family planning outcomes in underdeveloped village contexts.